Ideology in Advertisement: A Critical Discourse Analysis of Selected Nepali Advertisements - Sharma, Prakash (Pragnya Sarathi, 2023)
This paper explores the way ideology is embedded in the underlying structure of advertisements, applying Critical Discourse Analysis (CDA) as a theoretical tool focusing on the ideas of Michael Foucault and Norman Fairclough. Four advertisements telecasted in Nepal Television are selected for the analysis. They represent four different fields such as jewelry shop, bathing soap, food supplement and electric cable. Following qualitative research design, this study has used critical, analytical and interpretative method for analyzing the textual data. Critical analysis of these representative advertisements has led to the conclusion that mass media discourse is a fertile playground for ideological games. Keeping in mind the social structure of Nepalese society, they all in a united form impart patriarchal ideology to the audiences. This article proposes a solution to such biased representation. Language is being used as a means of imparting the patriarchal ideology and we should seek a solution from there. We should create critical linguistic awareness for the audience and empower them to resist all such misrepresentations. Resistance is essential for gender equality and only critical linguistic awareness can help create a just society.